2009
DOI: 10.1101/gad.1760209
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish miR-1 and miR-133 shape muscle gene expression and regulate sarcomeric actin organization

Abstract: microRNAs (miRNAs) represent ;4% of the genes in vertebrates, where they regulate deadenylation, translation, and decay of the target messenger RNAs (mRNAs). The integrated role of miRNAs to regulate gene expression and cell function remains largely unknown. Therefore, to identify the targets coordinately regulated by muscle miRNAs in vivo, we performed gene expression arrays on muscle cells sorted from wild type, dicer mutants, and single miRNA knockdown embryos. Our analysis reveals that two particular miRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
145
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(160 citation statements)
references
References 53 publications
13
145
2
Order By: Relevance
“…Interestingly, maternally inherited miRNAs appear to be rapidly down-regulated during the maternal-zygotic transition, raising the possibility that they are subject to similar forms of regulation as maternally inherited mRNAs. Beyond maternally inherited miRNAs, our analyses are also consistent with important early roles for a number of miRNAs, including miR-203, miR-1, and miR-133, which function to balance proliferation and differentiation during early development (Yi et al 2008;Mishima et al 2009). In contrast to previous results, we detected significant levels of let-7, raising the question as to its exact role in early development (Kloosterman et al 2004;.…”
Section: Discussion Mirna Expressionsupporting
confidence: 50%
See 1 more Smart Citation
“…Interestingly, maternally inherited miRNAs appear to be rapidly down-regulated during the maternal-zygotic transition, raising the possibility that they are subject to similar forms of regulation as maternally inherited mRNAs. Beyond maternally inherited miRNAs, our analyses are also consistent with important early roles for a number of miRNAs, including miR-203, miR-1, and miR-133, which function to balance proliferation and differentiation during early development (Yi et al 2008;Mishima et al 2009). In contrast to previous results, we detected significant levels of let-7, raising the question as to its exact role in early development (Kloosterman et al 2004;.…”
Section: Discussion Mirna Expressionsupporting
confidence: 50%
“…Previous work has shown that miRNAs play important functional roles during cell specification and differentiation (Giraldez et al 2005;Flynt et al 2007;Mishima et al 2009). In zebrafish, miRNA expression patterns have been extensively examined using direct cloning and microarray analyses (Giraldez et al 2005;Thatcher et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…MiRs function by base-pairing to a 'seed' sequence located in target mRNAs, mediating mRNA degradation or translational repression (Bartel, 2009;Filipowicz et al, 2008). In both mice and zebrafish, recent studies aimed at eliminating the function of an enzyme essential for general miR-processing, Dicer, have demonstrated important roles for miRs in embryonic myogenesis, because the resulting phenotype is decreased muscle mass and abnormal muscle fiber morphology (Mishima et al, 2009;O'Rourke et al, 2007). In addition, members of the miR1 and miR206, and miR133 families, referred to as muscle-specific miRNA (myomiRs) (Goljanek-Whysall et al, 2012;McCarthy, 2008), are known to regulate genes that participate in adult myoblast activation, including Histone Deacetylase 4, DNA Polymerase a and Connexin 43 (Anderson et al, 2006;Chen et al, 2006;Goljanek-Whysall et al, 2012;Kim et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Tropomyosin alpha-4 chain plays a central role, in association with the troponin complex, in the calcium-dependent regulation of vertebrate striated muscle contraction (Crabos et al, 1991). mir-1 expression in the muscle modulates cardiac and skeletal muscle proliferation and differentiation in zebrafish (Mishima et al, 2009) and humans (Koutsoulidou et al, 2011). Moreover, Nile tilapia mir-1 expression has been observed in skeletal muscle (Huang et al, 2012).…”
Section: Prediction Of Mirna Targetsmentioning
confidence: 99%